Organic facies and paleo-depositional environments of the Aptian–Albian Kazhdumi source rock in the Zagros basin of Iran. (November 2022) - Alipour, Majid
Abstract: The Kazhdumi Formation of SW Iran is considered as one of the main petroleum source rocks of the Cretaceous petroleum system. Despite an overwhelming body of research on the gross organic geochemistry of this formation, little is known about its organic facies and paleo-depositional environments. In this research, organic geochemical and sequence stratigraphic principals was used to throw light on the mechanisms controlling organic enrichment in the Kazhdumi Formation. Petrographic examinations revealed that the Kazhdumi organic-rich facies was deposited during times of relative sea-level rise and the related euxinia. In addition, the organic matter preserved in the Kazhdumi Formation varied strongly in type from SW to NE of the paleo-depositional settings. In contrast, organic-lean facies were accommodated within the Kazhdumi intra-shelf basin during periods of sea-level fall. These results have practical implications for future geochemical studies including oil-source correlations and petroleum system analysis. Graphical abstract: Image 1 Highlights: Kazhdumi Formation has strong organic facies variations. Euxinic conditions existed in the Kazhdumi intra-shelf basin. Organic-rich facies was deposited during highstand under euxinic conditions. Organic-lean facies was deposited during lowstand under oxic settings.